Powered‐two‐wheelers and smart cities: the case of variable message signs. Issue 14 (22nd February 2021) - Spyropoulou, Ioanna; Impersimi, Eriola
Abstract : At present, a number of smart urban mobility solutions exist and furthermore are emerging towards the design of smart cities offering equitable, green and efficient transport. As this concept addresses the needs of all travellers, it is essential to explore the relevance of existing and proposed smart solutions for distinct user categories. Powered‐two‐wheelers (PTWs) comprise a distinct vehicle category exhibiting specific movement dynamics and characteristics while exhibiting considerable presence in urban areas and increasing ownership trends during the recent years. Thus, PTW needs should be identified and considered in the design of smart cities. This study explores PTW diversion behaviour considering variable message signs (VMS) operation. Relevant data was collected through a stated preference questionnaire survey and diversion propensity was explored through the design of probit models. Survey results indicated that although PTWs believe that VMS fail to address their needs, their attitudes towards them are still positive. Model results exhibited that most of the information elements transmitted via VMS affect PTW diversion behaviour. Other contributory factors, considering PTW diversion included traffic code violation behaviour, rider 'flexibility', age, gender etc. Rider sub‐populations, considering riding on the pavement or pedestrianised areas and internet use for traffic information, were also explored.